2019
DOI: 10.3390/s19214788
|View full text |Cite
|
Sign up to set email alerts
|

SensorTalk: An IoT Device Failure Detection and Calibration Mechanism for Smart Farming

Abstract: In an Internet of Things (IoT) system, it is essential that the data measured from the sensors are accurate so that the produced results are meaningful. For example, in AgriTalk, a smart farm platform for soil cultivation with a large number of sensors, the produced sensor data are used in several Artificial Intelligence (AI) models to provide precise farming for soil microbiome and fertility, disease regulation, irrigation regulation, and pest regulation. It is important that the sensor data are correctly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 17 publications
0
17
0
4
Order By: Relevance
“…A mutual-test consists of at least one sensor and one actuator under test [ 23 ]. An example is the window control where the CO 2 sensor ( Figure 16 a) controls an electric window ( Figure 16 b) to enhance the air quality in a room [ 24 ].…”
Section: The Spectalk Acceptance Testsmentioning
confidence: 99%
“…A mutual-test consists of at least one sensor and one actuator under test [ 23 ]. An example is the window control where the CO 2 sensor ( Figure 16 a) controls an electric window ( Figure 16 b) to enhance the air quality in a room [ 24 ].…”
Section: The Spectalk Acceptance Testsmentioning
confidence: 99%
“…However, the problem is the false detection probability of IoT sensors to the gateway. Then, the authors in [19] have presented a solution called SensorTalk to automatically detect the potential sensor failures and semi-automatically calibrate the aging sensors. The solution showed that the false detection probability of IoT sensors to the gateway was reduced to less than 0.7 %.…”
Section: Smart Farmingmentioning
confidence: 99%
“…To overcome high environmental temperatures, many solutions have recently been suggested by various countries. These include the building of smart farms that are controlled by computer systems based on artificial intelligence (AI) and the development of genetically engineered crops [10][11][12]. However, most of these technologies have numerous limitations, such as high cost, large space requirements, and human health and safety concerns [13].…”
Section: Introductionmentioning
confidence: 99%